A flexible and simplified visual language programming to harmonious sound rendering using l-systems - Chen, Kim Lim; Kian, Lam Tan (2016)
Lately, computer-music learners have been attracted to the applications of L-Systems in rendering harmonious music. However, the current available systems such as LMUSe, could only render harmonious sound if the L-Systems grammars are known by the user.Besides, in producing harmonious sound in LMUSe, stochastic and context-sensitive L-Systems are combined in a single step and therefore, it is hard for the computer-music learners to apply L-Systems.In this paper, we propose a simple and flexible visual language programming for sound rendering so that the harmonious sound can easily be generated compared to LMUSe. Furthermore, with this framework, the computer-music and L-Systems learners do not need to have prior knowledge in both areas. Moreover, the stochastic and context-sensitive grammars are applied step-by-step as part of the methodology to enhance the understanding of the process involved. The implementation of the framework has six phases using the data-flow programming model.Based on the evaluation, it was found that the users could easily understand, appreciate and learn the process of applying stochastic and context-sensitive grammars in generating harmonious sound.